Determinants of foreign direct investment in the Visegrad group countries after the EU enlargement - Su, Weihua; Zhang, Dongcai; Zhang, Chonghui; Abrhám, Josef; Simionescu, Mihaela; Yaroshevich, Natalya; Guseva, Valentina (Technological and Economic Development of Economy, 2018)
Considering the role of foreign direct investment (FDI) inflows in the sustainable development of a country, the main aim of this paper is to identify some macroeconomic factors that positively or negatively influence FDI in Visegrad group countries after the European Union (EU) enlargement in 2004. We employed two types of approaches in our analysis: i) time series and ii) panel data approach. According to the generalized ridge regressions estimated in Bayesian framework, the perceived corruption was a factor that influenced FDI in all the countries. In Poland, Czech Republic and Slovakia corruption came through as a serious obstacle for FDIs since 2005, but this was not the case for Hungary. Even if Hungary is perceived as a country with high influence, foreign investors seem no to care about this fact and are more interested in the quality of human resources and the possibility to increase exports. Our panel approach based on a panel ARDL model identified a significant relationship between FDI, corruption index and labour force with advanced education however this causality was only detected in the long run. According to the Granger causality in panel, the attraction of FDI inflows succeeded in generating changes in total tax rate, but the issues related to corruption were not reduced at an acceptable level for foreign investors in Poland, Slovakia, and the Czech Republic.